Determination of rock elastic parameters using VP/VS relation-ship for escravos area, Niger delta, Nigeria - Ajayi, Tobiloba; Adepelumi, Abraham; Agih, Christain (International Journal of Advanced Geosciences, 2014)
The elastic properties of sedimentary rocks in the Escravos area, Niger delta, Nigeria, have been computed for six boreholes drilled to a maximum of 22 m. Compressional wave (Vp), Shear wave (Vs) velocities and density (?) values were computed for the lithologies at the six different boreholes. The elastic properties were estimated using the computed Vp, Vs and ? values. Empirical relations between the derived elastic and physical properties of the subsurface lithologies encountered in the boreholes were established. The results show three distinctive layers comprising Sand, Sandy clay and Clayey sand existing in the boreholes. The computed values of the elastic properties show that the formation encountered in the wells are moderately dense and saturated with water. A distinct linear relationship existing between Vp / Vs was observed; while an exponential relationship was derived for ?/Vs. Empirical relationships derived from this study for Vp - Vs is given as Vs = 0.902Vp - 1164, and for Vs - Poisson’s is given as ? = -1E-07Vs2 - 4E-05Vs + 0.502. The values of allowable bearing capacity and the settlement suggest that the study area is able to support engineering construction. Empirical relations established for Vp - Vs and Vs - Poisson’s is characteristics of sedimentary terrain, and can be used within the Escravos area, Niger Delta, Nigeria. Keywords: Allowable Bearing Capacity, Elastic Properties, Empirical Relations, Settlement.